Demographic bonus in Bali: hopes and challenges in reproductive health - I Made Darmayasa; IGN Harry Wijaya Surya; Made Bagus Dwi Aryana (Indonesian Journal of Perinatology, 2021)
Background: Bali experienced an earlier demographic bonus and a longer duration than the national one. The demographic bonus provides both hope and challenges from a reproductive health perspective, especially in the current Covid-19 pandemic. Methods: Extracted from various sources, analyzed and presented in the form of a description. Result: In the period 1960-2000, the population growth rate in Bali continued to decline, but from 2000 to 2010, it increased again to 2.14. The age group below 50 years reaches 80%, the distribution is 30% under the age of 18 years, then 24% at the age 19-35 years, and 24% for the age group 35-50 years. In 2020 Bali entered the demographic bonus with the lowest dependency ratio between 42.2% - 43.3%. Bali's life expectancy rate reached 70.61 years in 2010 and is predicted to be 71.68 years in 2018. Based on the Regency/City of Bali Province's projected population in 2010-2020, the number of seniors in Bali in 2020 is 11.51%. The challenges faced include: 1. Knowledge of adolescents about reproductive health, 2. High number of the population in productive age accompanied by an understanding of reproductive health is still low. 3. Disease awareness of various pathological conditions in pregnancy is still low, coverage of contraceptive use is still low, causing pregnancy without planning, unwanted and high risk, 4. Low quality of antenatal care, 5. There are still many pregnant people, and giving birth without financing pattern, 6. Population mobility, many pregnant women who come to Bali, are not equipped with population data/identities, including family cards, 7. The increasing number of people over 60 years of age are unproductive, unhealthy, and not independent. These challenges will burden the family and or the government, especially if they do not have a good financing pattern. Conclusion: The demographic bonus in Bali occurs earlier than in some other regions in Indonesia due to success in managing population programs. This bonus does not guarantee the success of development in the overall sense of the Covid-19 pandemic era. Bali still has to strive hard to realize its development hopes and solve existing and real challenges.